2019
DOI: 10.22424/jmsb.2019.37.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action of Raphanus raphanistrum subsp. sativus (radish) Extracts against Foodborne Bacteria Present in Various Milk Products: A Preliminary Study

Abstract: Seeds and leaves of Raphanus raphanistrum subsp. sativus (radish) are known to contain "raphanin," which has the potential to inhibit pathogenesis associated with foodborne pathogenic bacteria and fungi. In this study, ethanol extracts from R. raphanistrum subsp. sativus (radish) powder was evaluated for antimicrobial action against 6 different foodborne pathogenic bacteria. The current study demonstrated the potential of R. raphanistrum subsp. sativus (radish) in inhibiting the growth of Salmonella enteritidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Researchers in India found that white radish has powerful effects against the bacteria Agrobacterium rhizogenes (Muthusamy and Shanmugam, 2020). There was a study done in Korea that found that the White radish ethanol extract was efficient against Listeria monocytogenes, Salmonella Enteritidis, Escherichia coli, Cronobacter sakazakii, Bacillus cereus, and Staphylococcus aureus (Lim et al, 2019). Similar to these other researchs, we found that white radish tuber pieces effectively combat various bacterial and fungal strains.…”
Section: Antimicrobial Activitysupporting
confidence: 82%
“…Researchers in India found that white radish has powerful effects against the bacteria Agrobacterium rhizogenes (Muthusamy and Shanmugam, 2020). There was a study done in Korea that found that the White radish ethanol extract was efficient against Listeria monocytogenes, Salmonella Enteritidis, Escherichia coli, Cronobacter sakazakii, Bacillus cereus, and Staphylococcus aureus (Lim et al, 2019). Similar to these other researchs, we found that white radish tuber pieces effectively combat various bacterial and fungal strains.…”
Section: Antimicrobial Activitysupporting
confidence: 82%
“…After drying, these peels were ground into a fine powder, and the milled parts were kept in clean plastic containers under a moisture-free condition until required for extraction. 9 Solvent extraction of radish root peel Ethanol and methanol extracts of radish root peels were prepared as described, 5 using 80% of both solvents. The Radish root peel sample was weighed (1 g) and added to 50 mL of each solvent.…”
Section: Preparation Of Radish Plant Materialsmentioning
confidence: 99%
“…Over the next years, knowledge about the antibacterial compounds contained in radish seeds was extended. The following pathogens, i.e., Streptococcus pyogenes , E. coli , Salmonella enteritidis 110, Cronobacter sakazakii KCTC 2949, B. cereus ATCC 10876 and Staphylococcus aureus ATCC 6538 are sensitive to radish metabolites ( Jadoun et al, 2016 ; Lim et al, 2019 ). The effect of red-peel radish root extract on 52 food-borne bacteria confirmed the presence of compounds with antimicrobial activity ( Jadoun et al, 2016 ; Kaymak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%